The Early Results of Vertebral Pathological Compression Fracture of Extra- nodal Lymphoma with HIV-positive Patients Treated by Percutaneous Kyphoplasty - Sun, Sheng; Xu, Biao; Zhang, Qiang; Zhao, Chang-song; Ma, Rui; He, Jie; Zhang, Yao (Current HIV Research, 2020)
Background: Vertebral pathological compression fracture involving extra-nodal lymphoma impacts negatively on the quality of life of HIV-positive patients. The choice of a safe and effective approach to palliative care in this condition remains a challenge. Objective: The purpose of this study was to investigate the safety and efficacy of percutaneous kyphoplasty (PKP) in the treatment of vertebral pathological compression fracture of extra-nodal lymphoma in HIV-positive patients. Methods: A retrospective analysis, from January 2016 to August 2019, was performed on 7 HIVpositive patients, 3 males and 4 females, with extra-nodal lymphoma with a vertebral pathological compression fracture. The patients were treated using percutaneous kyphoplasty in our hospital. Preoperative assessment of the patients was conducted regarding their hematological profile, biochemical indicators, liver and kidney function, blood coagulation function, CD4+T lymphocyte count and viral load. Subsequently, the patients were placed on highly active antiretroviral therapy (HAART) and rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (RCHOP) regimen. Besides, antibiotics, nutritional support and immune-modulating drugs were also administered, rationally. Postoperatively, the height of the anterior edge of the injured vertebrae, Visual Analogue Scale (VAS) and Oswestry Disability Index (ODI) values were evaluated. Patients were also monitored for any complications related to the operation. Results: The average CD4+T cell count for the patients was 164 (range 114 247 / ul), while the viral load was 26,269 (range 5,765 82,321 copies/ul). All patients received nutritional and immune support and registered significant improvements in the levels of ALB and Hb (P<0.05). In all cases, the operation was uneventful with neither cement leakage nor toxic reactions observed. Similarly, no opportunistic infections, other complications or deaths were reported. The height of the anterior vertebral body and the ODI score of the injured vertebrae were significantly improved immediately after surgery (P<0.05). Compared to the preoperative VAS (7.71±1.11), postoperative values were significantly reduced immediately after surgery (3.85±0.90) and at 2 weeks, 1 month and 6 months post-surgery: 2.71±0.76, 3.29±1.11, and 4.00±0.82, respectively (P<0.01). Conclusion: Supported with appropriate perioperative treatment measures, PKP is safe and effective in the treatment of pathological vertebral compression fracture due to extra-nodal lymphoma in HIV-positive patients.
Keywords: HIV